Development of a vuilleumier refrigerator with crank drive mechanism based on experimental and numerical study. (September 2021) - Cheng, Chin-Hsiang; Feng, Jian-Hua; Huang, Jhen-Syuan
Research highlights: Development of Vuilleumier refrigerator by theoretical and experimental methods. A real Vuilleumier refrigerator is built and tested. At 22 bar, 600 rpm, operating temperatures 900 K and 276 K, 221 K is reached. A novel thermodynamic model is developed and validated. Abstract: The present paper is focused on development of the thermodynamic model and a heat-driven Vuilleumier refrigerator. Thermodynamic properties and performance are predicted by thermodynamic model. On the other hand, a prototype Vuilleumier refrigerator with crank drive mechanism is built and the performance is measured. In the thermodynamic model, the refrigerator is divided into five working spaces for analysis, including hot chamber, hot regeneration chamber, middle chamber, cold regeneration chamber and cold chamber. Also, the influence of clearance leakage between middle chamber and buffer chamber is investigated. The effects of geometrical parameters, charged pressure, rotating speed, heating temperature, cooling temperature and heat loading on the cold head temperature are evaluated. In addition, the numerical results and the experimental data under different operating parameters are compared for model validation. As the Vuilleumier refrigerator operated at 22 bar pressure, 600 rpm rotating speed, 900 K heating temperature and 276 K cooling temperature, the cold head can reach a zero-load temperature of 221 K. When a 0.7 W heating load is applied on the cold head, cold head temperature of 252.6 K and coefficient of performance of 0.0068 can be obtained.